Staphylococcus aureus Population Structure and Genomic Profiles in Asymptomatic Carriers in Switzerland - Etter, Danai; Corti, Sabrina; Spirig, Simona; Cernela, Nicole; Stephan, Roger; Johler, Sophia (Frontiers in Microbiology, 2020)
Staphylococcus aureus is a leading cause for clinical infections and food intoxications, causing over 100'000 yearly cases of bacteremia in the US and 434 food-borne outbreaks in the EU. Approximately 30% of the population permanently carry S. aureus asymptomatically in their nasal cavity. The risk of infection and transmission to foodstuffs or the environment is higher in individuals that are nasally colonized. In addition, S. aureus can acquire various antimicrobial resistances leading to therapeutic failure, additional medical costs and fatalities. Methicillin-resistant S. aureus (MRSA) cause a considerable burden of disease in humans and animals. MRSA carriage has been associated with animal and in particular livestock contact. Extensive current data on the virulence gene profiles, as well as data on antimicrobial resistance determinants is crucial in developing effective strategies to mitigate the burden of disease. To this end, we screened the anterior nares of 160 test subjects (87 pupils and 73 members of farmer families) in Switzerland for S. aureus carriage. A total of 73 S. aureus isolates were obtained. Factors such as exposure to farm or companion animals and personal medical history were recorded using a questionnaire. Using a DNA microarray, isolates were assigned to clonal complexes, and virulence and resistance gene profiles were determined. The collected strains were assigned to 20 clonal complexes, amongst others CC1, CC7, CC8, CC15, CC30, CC45, CC97, and CC398. Two MRSA strains and one multiresistant isolate carrying genes blaZ/I/R, InuA, aadD, tetK, and fosB were isolated from farmers with intensive exposure to animals. Strains carrying pvl, causing severe skin lesions and necrotizing pneumonia, as well as tetracycline, erythromycin, and kanamycin resistance genes were found in individuals that had taken antibiotics during the last year. A variety of superantigenic toxin genes was detected, including amongst others, the toxic shock syndrome toxin (tst1), and various enterotoxins (sea, sec, sel, and the egc cluster). Contact to chickens was identified as a significant factor contributing to S. aureus colonization.